2017
DOI: 10.1038/srep41021
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Tolerability of Different Recommended Doses of PPIs and H2RAs in GERD: Network Meta-Analysis and GRADE system

Abstract: Proton pump inhibitors (PPIs) and histamine-2-receptor antagonists (H2RAs) are used for gastro-esophageal reflux disease (GERD); however, the clinical evidence for treatment is poor. We evaluated the effectiveness and tolerability of different doses of PPIs, H2RAs and placebo in adults with GERD. Six online databases were searched through September 1, 2016. All related articles were included and combined with a Bayesian network meta-analysis from randomized controlled trials (RCTs). The GRADE systems were empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 67 publications
1
14
0
Order By: Relevance
“…Zhang et al . reported that PPIs are more effective than H 2 RAs and that esomeprazole (40 mg) was the most effective treatment in the study . In our study, the OR to placebo was also highest for esomeprazole (40 mg) among the PPIs with the same dosage as in the Zhang et al .…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Zhang et al . reported that PPIs are more effective than H 2 RAs and that esomeprazole (40 mg) was the most effective treatment in the study . In our study, the OR to placebo was also highest for esomeprazole (40 mg) among the PPIs with the same dosage as in the Zhang et al .…”
Section: Discussionsupporting
confidence: 61%
“…Network meta‐analyses of RCTs, comparing PPI efficacy in healing GERD, were previously conducted by Zhang et al . and Li et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, Li et al [45] and Zhang et al [46] reported the comparative efficacy of different PPIs in healing GERD and relieving its symptoms, as well as the acceptability/tolerability of PPIs by network meta-analysis. However, to our knowledge, the comparative efficacy of different PPIs for the maintenance treatment of GERD and that of PPIs and vonoprazan have not been conducted to date.…”
Section: Discussionmentioning
confidence: 99%